Influence of technological factors on foam cement concrete formation mixtures and product properties/Technologinių veiksnių įtaka putų cementbetonio formavimo mišinių ir gaminių savybėms - Laukaitis, Antanas (Journal of Civil Engineering and Management, 1997)
In this paper, 250–500 kg/m3 density autoclave hardened foam cement concrete production technology influence on some of its properties made using Portland cement is discussed. Raw materials composition is given in Table 1. Foam for the production of good quality foam concrete products should meet the following requirements: 1) be stable and mechanically strong, because it should hold the foam concrete weight until the mixture hardens; 2) be temperature resistant, because due to binder hydration the mass temperature reaches 50–60 °C; 3) have a high recurrence, because the foam components slow down the binders hydration. The experiments have shown that the best foamier is Sulfonol and bone glue as a stabiliser for autoclave foam concrete. The formation of fixed density foam concrete products is very complicated problem. The foam cement concrete density dependence on its formation mixture density is derived by equation 4. When 1 dm3 foam cement concrete mixture is weighed, one can calculate the foam cement concrete density and immediately correct it, if necessary. We prepared foam with a recurrence of 20 and 50 and Sulfonol concentration of 1 and 2 % (Sulfonol and bone glue ratio 1: 0.2) to determine the foamier amount influence. The same amount of foam was used (3 dm3/kg per solids), when foam cement concrete mixtures were formed. The results given in Table 2 show that, when different amount of surface active materials are used, we get different foam and foam cement concrete mixtures as well as product density values. Foam cement concrete mass due to different foam concentrations and recurrence slow down the binding materials hydration and a mass temperature difference is observed (Fig 1). It was found that the block can be cut up in products when the mass plasticity strength reaches 0,0012 N/mm2. Product compression strength increases by 10–20 % (Table 2) when higher recurrence foam is used. A 2% Sulfonol foamier (Sulfonol: bone glue 1: 0.2 composition) was chosen for further experiments, using whipped foam recurrence of 50. Foam cement concrete densi-ty depends on the amount of foam used (Fig 2). Foam Reccurency influence on Foam cement concrete properties is given in Table 3. The use of larger V/K ratio, contrary to gaseous cement concrete, does not lower the foam cement concrete product density, because the same amount of foam is added to a larger volume. The most optimal way to produce foam cement concrete is when the V/K ratio changes from 0.6 to 0.7 (Fig 2). Foam cement concrete density dependence on technological operations regressive equation was derived. Closed pores dominate in the foam cement concrete structure and that is the reason why its heat conductivity is lower. Equal density gaseous silicate concrete, foam gaseous silicate concrete and foam cement concrete was made for comparison of results. The results (Table 4) show that foam cement concrete has the best heat conductivity and it is confirmed by the samples air resistance. Article in Lithuanian. First Published Online: 26 Jul 2012